Front-end hybrid designs for the CMS Phase-2 Upgrade towards the production phase. (1st April 2022) - Kovacs, M.; Blanchot, G.; Gadek, T.; Hollos, A.; Dominguez, I.; Zografos, A.; ,
Abstract: Sixteen thousand 2S front-end hybrids and twelve thousand PS front-end hybrids will be produced for the CMS Tracker Phase-2 upgrade. The hybrids consist of flip-chips, passives and mechanical components mounted on a flexible substrate, laminated onto carbon-fibre stiffeners with thermal expansion compensators. In the prototyping phase, several critical issues have been solved to manufacture these complex circuits. Final designs are now reaching readiness for the full-scale production. Lessons learned during the prototyping phase and different improvements implemented for manufacturability will be presented in this contribution.